Mutagenesis and functional analysis of SotB: A multidrug transporter of the major facilitator superfamily from Escherichia coli - Zhai, Guoqing; Zhang, Zhengyu; Dong, Changjiang (Frontiers in Microbiology, 2022)
Dysfunction of MFS Multidrug (Mdr) transporters can lead to a variety of serious diseases in human. In bacteria, such membrane proteins are often associated with resistance. However, as one of the MFS Mdr transporters, the physiological function of SotB from Escherichia coli is poorly understood to date. To better understand the function and mechanism of SotB, we carried out a systematic study on this MFS Mdr transporter. In this study, we find that SotB can directly efflux L-arabinose in E. coli by overexpressing sotB gene combined with cell based radiotracer uptake assay. Besides, the surface plasmon resonance (SPR) studies, together with precise molecular docking analysis, reveal the following: (i) the functional importance of E29 (protonation), H115/N343 (substrate recognition) and W119/S339 (substrate efflux) in the SotB mediated export of L-arabinose, and (ii) for the first time find that D-xylose, an isomer of L-arabinose, likely hinders the binding of L-arabinose with SotB as a competitive inhibitor. Finally, by analyzing the structure of SotB2 (shares 62.8% sequence similarity with SotB) predicted by AlphaFold 2, the different molecular mechanism of substrate recognition between SotB and SotB2 is explained. To our knowledge, this is the first systematic study of MFS Mdr transporter SotB. The structural information, together with the biochemical inspections in this study, provides a valuable framework for further deciphering the functional mechanisms of the physiologically important L-arabinose transporter SotB and its family.